2003
DOI: 10.1046/j.1365-2303.2003.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory reproducibility of atypical squamous cells of undetermined significance report: a national survey

Abstract: The study was aimed at assessing interlaboratory reproducibility in the reporting of cervical smears in the atypical squamous cells of undetermined significance (ASCUS) category. A set of 50 selected slides circulated among 89 laboratories, currently involved in population-based screening programmes for cervical cancer, which provided a diagnostic report according to four main reporting categories based on the 1991 Bethesda system. Interlaboratory agreement was determined according to kappa (K) statistics: ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 16 publications
0
14
0
6
Order By: Relevance
“…The decision to refer all patients with minor cytologic abnormalities for colposcopy implies a large number of unnecessary colposcopies and colposcopy-directed biopsy and has a negative impact on screening costs. Moreover, as confirmed recently in a large Italian study, 2 the reproducibility of ASCUS reports is quite low, and the action prompted by an ASCUS report would be decided on a local basis and should be based on the observed PPV for Ͼ CIN2 lesions. 3 Criteria to qualify ASCUS 4 findings (Bethesda System, 2001; ASC-US and atypical squamous cells-cannot exclude HSIL [ASC-H]) have been proposed to improve the specificity of referral to colposcopy while keeping a high sensitivity level.…”
mentioning
confidence: 97%
“…The decision to refer all patients with minor cytologic abnormalities for colposcopy implies a large number of unnecessary colposcopies and colposcopy-directed biopsy and has a negative impact on screening costs. Moreover, as confirmed recently in a large Italian study, 2 the reproducibility of ASCUS reports is quite low, and the action prompted by an ASCUS report would be decided on a local basis and should be based on the observed PPV for Ͼ CIN2 lesions. 3 Criteria to qualify ASCUS 4 findings (Bethesda System, 2001; ASC-US and atypical squamous cells-cannot exclude HSIL [ASC-H]) have been proposed to improve the specificity of referral to colposcopy while keeping a high sensitivity level.…”
mentioning
confidence: 97%
“…This interlaboratory and interobserver variability has been found in other studies. Confortini et al [23] showed a low interlaboratory reproducibility in the category ASC-US (kappa = 0.34). Gatscha et al [24] showed in their review that, out of 632 smears first diagnosed with atypical squamous, only 200 cases (32%) showed interobserver agreement, which demonstrated the low reproducibility of this diagnostic category.…”
Section: Discussionmentioning
confidence: 99%
“…Ha sido claramente documentado que las células escamosas atípicas de significado indeterminado es la interpretación menos reproducible de todas las categorías del sistema Bethesda (19,20). Por lo tanto, estas diferencias pueden reflejar dificultades en la implementación de criterios para la lectura de las citologías con esta categoría y sugiere la necesidad de un sistema que evalúe la reproducibilidad de los resultados de células escamosas atípicas de significado indeterminado en la citología en nuestro medio.…”
Section: Discussionunclassified